How forage grain ratoon rice improves the grain yield during the ratoon season - Gai, Panpan; Chen, Yuanwei; Sun, Xin; Chen, Hongjing; Yang, Desheng; Ren, Miaofei; Liu, Lei; Wang, Weiqin; Zheng, Hua-bin; Tang, Qiyuan (Frontiers in Plant Science, 2024)
Introduction In recent years, with the rapid expansion of ratoon rice production in Hunan, a unique ratoon rice-based production system, forage-grain ratoon rice (FG-RR), has been newly developed. Ratooning rice is a season of rice harvested by utilizing the dormant buds on the rice stubble left after harvesting the first season of rice to sprout and grow. Therefore, the characteristics of stalks themselves are crucial for the production of ratoon rice. The cutting period and higher stubble height directly affect the characteristics of ratoon rice stubbles. Based on this, we conducted the following research. Methods In 2021 and 2022, field experiments were conducted in central China to study the effects of different cutting periods and stubble height on the regeneration rate and nutrient content of ratoon crops. The treatments included two cutting periods (10 days after heading in the first season and 30 days after heading in the first season, respectively referred to as T10 and T30) and two stubble heights (10 cm and 30 cm, respectively referred to as H10 and H30). Results Compared with the T30H30 treatment, T10H10 and T10H30 increased grain yield by 48.1%, 41.7%, 73.1%, and 65.2% in the two-year ratoon seasons, while T30H10 reduced grain yield by 30.9% and 19.5% in the two years, respectively. Early cutting increased the panicles, spikelets per panicle, and filled grain rate to varying increase, while higher stubble height increased panicles but decreased spikelet panicle. On the one hand, early cutting and higher stubble height increased the dry and fresh weight, nonstructural carbohydrates (NSCs), organic carbon (C), and nitrogen content of rice stalks, thereby improving the regeneration rate of ratoon rice. On the other hand, early cutting and higher stubble height retention increased the accumulation of nitrogen in rice stubble throughout the entire growth period and facilitated the transport of nitrogen to the mature panicles. Discussion Therefore, appropriate early cutting and higher stubble height retention are the keys to improving the grain yield and stability of ratoon rice.